"There's Shari'a, and there's Life": A Field Study on the Diffusion, Acceptance and Rejection of Fiqh al-Aqalliyyat al-Muslima at Reykjavik's Grand Mosque. Issue 3 (3rd July 2018) - Shavit, Uriya; Spengler, Fabian
Abstract: In recent years, considerable academic attention has been devoted to fiqh al-aqalliyyat al-Muslima, the field of jurisprudence that addresses the unique challenges faced by Muslims living as minorities. However, little has been written on the ways fatwas are diffused, accepted, and rejected across European Muslim communities. Through a field study conducted at Reykjavik's Grand Mosque and rival local mosques from 17 September 2017 to 15 October 2017, the present article aims to contribute to bridging this scholarly gap. Drawing on theories from media studies and social psychology, the article reveals the non-structured and a-hierarchical ways through which Islamic norms are determined by mosque attendees. It demonstrates the reluctance of mosque attendees to privilege specific authorities on religious law; that they are informed by a plethora of traditional and global forms of authority; and that rather than adhere to and abide by a specific coherent doctrine, they intuitively shift between different approaches based on circumstances and needs.